"Caring for my family integrity": Fertile couples' first childbearing experience in the urban society of Mashhad, Iran. (March 2015) - Khadivzadeh, Talat; Latifnejad Roudsari, Robab; Bahrami, Masoud; Taghipour, Ali; Abbasi Shavazi, Jalal
Abstract: Background : This qualitative study was conducted to discover fertile couples' experiences of having their first child in the urban society of Mashhad, Iran. Methods : In this grounded theory study, 45 participants were selected. In-depth interviews were conducted at health centres, homes and workplaces. Data analyses were carried out adopting Strauss and Corbin's mode of analysis through a constant comparative method applying open, axial and selective coding using MAXqda software. Study rigour was verified via prolonged engagement with participants, member check and debriefing with peers. Results : The core category that describes couples' experience of having their first child was 'caring for my family integrity'. The process of first-time childbearing included four interrelated stages: (1) gaining confidence about the spouse's capability for being a parent, (2) evaluating situational conditions to make a decision whether to try to become pregnant, (3) managing childbearing across the life course and (4) parental role attainment. Conclusion : Couples' decisions about having their first child are influenced by their mutual relationship and the results of their evaluation of a variety of circumstantial, economic, child-training abilities and health-related conditions. Both planned and unplanned events influence childbearing experiences. It is important to comprehend the four-stage process and apply it in reproductive health care especially in the delivery of family planning services.